2016
DOI: 10.5935/0103-5053.20160035
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of β-Carbolines with DNA: Spectroscopic Studies, Correlation with Biological Activity and Molecular Docking

Abstract: Quantitative interaction of twelve β-carboline derivatives with calf thymus deoxyribonucleic acid (ctDNA) using spectroscopic techniques was evaluated. The values of the binding constants (K b ) obtained for the complexes formed with the ctDNA ranged from 3.30 × 10 2 to 1.82 × 10 6 mol L −1 , being the β-carbolines with the N,N-dimethylaminophenyl group at position 1 the ones which presented the highest K b values. The binding mode between the β-carbolines evaluated and ctDNA was proposed from the KI assay, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Previous studies reported that β-carboline and a series of its derivatives (including harman alkaloids) inhibit DNA topoisomerases and interfere with DNA synthesis; They interact with DNA by groove binding and intercalation, which may lead to major structural changes in the DNA ( Nafisi et al, 2010 ). Further, they exert a pronounced antitumor activity against human tumor cells, including KB, DLD, NCI-H661, Hepa, and HepG2/A2 cell lines ( Prinsep et al, 1991 ; Shen et al, 2011 ; Silva et al, 2016 ). Glycodeoxycholic acid and taurodeoxycholic acid are important components of bile acid, and cause liver injury during cholestasis by inducing hepatocyte apoptosis via Fas-dependent and -independent mechanisms ( Higuchi et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that β-carboline and a series of its derivatives (including harman alkaloids) inhibit DNA topoisomerases and interfere with DNA synthesis; They interact with DNA by groove binding and intercalation, which may lead to major structural changes in the DNA ( Nafisi et al, 2010 ). Further, they exert a pronounced antitumor activity against human tumor cells, including KB, DLD, NCI-H661, Hepa, and HepG2/A2 cell lines ( Prinsep et al, 1991 ; Shen et al, 2011 ; Silva et al, 2016 ). Glycodeoxycholic acid and taurodeoxycholic acid are important components of bile acid, and cause liver injury during cholestasis by inducing hepatocyte apoptosis via Fas-dependent and -independent mechanisms ( Higuchi et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results are in agreement with same works in the literature that evaluated the correlation between interaction with DNA (K b ) and values of biological activity. Silva et al [24] obtained a linear relation from logK b between ctDNA and β-carboline derivatives with IC 50 values (μM) for six human tumor cell lineages, with determination coefficients (r 2 ) from 0.5360 to 0.9600. In a similar evaluation, da Silva et al [57] observed a linear relation from logK b between ctDNA and Schiff bases with GI 50 values (μg·mL −1 ) for seven human tumor cell lines, with correlation coefficients (r) from −0.9778 to +0.8693.…”
Section: Resultsmentioning
confidence: 99%
“…Computational methodologies, such as molecular docking, have been employed to providing new scaffolds with high potency and good tolerance [23] . After molecular dynamic completion, the optimized ct-DNA structure with the lowest RMSD value was used in this study [24] . Molecular docking was performed in tentative to observe some aspects in the formation of complexes, such as nitrogenous bases involvement, binding mode, type of interaction, and best conformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding affinity of β -carboline derivatives ( 4B , 6i , 4D , and 6u ) to DNA were investigated through thermal denaturation experiments. Small molecules interact with DNA through the intercalation mode, which makes the DNA double helix more stable, thereby increasing the melting temperature ( T m ) [ 44 ]. Therefore, the thermal denaturation experiment provides a simple and effective method for detecting DNA-binding affinity.…”
Section: Resultsmentioning
confidence: 99%